Simultaneous determination of bisphenol A, aflatoxin B1, ochratoxin A, and patulin in food matrices by liquid chromatography/mass spectrometry. (17th February 2013) - Song, Wenlu; Li, Charlie; Moezzi, Bahman
<x xml:space="preserve">Abstract</x> RATIONALE Bisphenol A has been widely used in plastic containers and this has raised safety concerns for fetuses, infants, and young children. Aflatoxin B1, ochratoxin A, and patulin are among the most toxic regulated mycotoxins found as contaminants in agricultural crops and animal products. To facilitate the analysis of these chemicals for regulatory purposes, we have developed an analytical method enabling their simultaneous detection in beverages and food products. METHODS Analytes were extracted from food matrices such as cereal, peanut butter, cereal‐based baby formula and fruit juices, and enriched by solid‐phase extraction (SPE). Samples were analyzed by liquid chromatography/mass spectrometry using negative electrospray ionization with selected reaction monitoring, and matrix‐matched external calibration was used for quantitation. RESULTS The method was validated by analysis of five types of food and beverage samples fortified with different levels of these analytes. The SPE clean‐up and matrix‐matched external calibration were critical for the success of this method. The quantitation limits for these analytes ranged from 0.08 to 2.0 ppb, and the overall recoveries of the analytical method were within 66 to 127%. CONCLUSIONS This quantitative method provided several advantages including minimal sample pretreatment, rapid and simultaneous analyte determination, high sensitivity and confirmatory identification. This method could be applied to a variety of food and beverages matrices where bisphenol A and these three mycotoxins may be present in suspect food products. Published 2013. This article is a US Government work and is in the public domain in the USA.